Fenomena gejolak ekonomi pada sektor perdagangan dan sektor pariwisata: studi perbandingan sebelum dan selama Covid-19 - Normasyhuri, Khavid; Habibi, Ahmad; Anggraeni, Erike (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study compares the turmoil that occurred in the trade sector and the Indonesian tourism sector before and during the COVID-19 outbreak. The research method used is quantitative with a comparative approach. The data used is secondary data sourced from the Ministry of Trade of the Republic of Indonesia and the Ministry of Tourism of the Creative Economy of the Republic of Indonesia. This study uses a statistical test tool in the form of SPSS Version 21 with Paired Sample T-Test. The results showed significant differences in the trade sector before the onset of covid-19 and during the occurrence of covid-19. This occurred from the spread of Covid-19, which caused supply and demand shocks. The decline in trade reflects rising trade costs, disruptions to transportation, logistics, supply chains, and trade restrictions. Furthermore, there are significant differences in the tourism sector before the onset of covid-19 and during covid-19. This happened due to travel restrictions imposed by the government, causing a reduction in both domestic and international travel. The spread of the COVID-19 pandemic has caused foreign tourists to cancel trips and book tickets on a large scale, and the reluctance of tourists to visit is influenced by concerns about the impact of tourism travel during the pandemic.